Narses and the Lombards (Vade Nobiscum, tom XX/2019: Studia z historii politycznej i wojskowej, 2019)
First contact between Narses and Lombards took place probably during the campaign againist Ostrogoths in 552 when Lombardsfought under his command. They seemed to be brave soldiers but simultaneously became authors of many assaults on local people and were sent back to their native Pannonia. According to some sources (e.g. Isidore of Sevilla, Liber pontificalis) Narses invited Lombards to Italy in 568 because he wanted to take his revenge on empress Sophia. This version however is not confirmed by the majority of earliest sources (e.g. Marius of Avenches, Gregory of Tours, all byzantine sources). Nonetheless the narration about collaboration between the byzantine commander and Lombards should not be all rejected because it is present in many independent and quite reliable sources. In connection to the hypothesis created by Neil Christie there is possibility to propose its extension which could unite contradict narrations. This extension could solve the problem which is contradiction between hypothetical deliberate settling of Lombards and contemporary policy of empire under Justin II which was very unfavorable for barbarians. It is possible that Narses contacted with Lombards in good faith, but did it against the will of imperial pair. The result was his removal. It is possible too that the attempt to settle Lombards was not the effect of the invitation but only failed attempt of fixing the situation caused by their lawless arrival.